The Role of Parents in Encouraging Early Childhood Communication Skills - Hafnan Aziz Hasibuan (QAULAN : Jurnal Komunikasi dan Penyiaran Islam, 2024)
Technological advancements are becoming more advanced and sophisticated. This has a variety of effects on people's lifestyles, including their mental and behavioral habits. Gadgets are one of the technical advancements that have an impact on people's minds. Devices are media that are employed as contemporary means of communication. Not only do gadgets affect adult thought processes and conduct, but they also have an impact on young children's behavior. Essentially, young children are content with the new things they discover through play. Children enjoy playing because it allows them to fully realize their potential. In Indonesia, most kids spend their time playing with electronics. Naturally, this has an impact on kids' development, particularly on how they learn to connect with others. Relationships that develop between groups of people who are connected by social activity and communication are referred to as social interaction. The purpose of this study is to describe how young children's social interaction skills are affected by their use of gadgets. Descriptive qualitative research methodology, which examines the current status of human groups, objects, situations, thought systems, or classes of occurrences, was employed in this study. The data was processed so that it could be included in a scientific work. The study's findings indicate that most kids use technology more for play than for learning. Children who initially like playing with their friends may alter as a result of these little things if they grow accustomed to receiving devices in place of playing with pals